2010
DOI: 10.1002/app.31771
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of polyethylene ionomer based nanocomposites

Abstract: Li and Zn ionomers of poly(ethylene-comethacrylic acid) were modified by two organically modified montmorillonites by melt mixing. In the nanocomposites (NCs), the increase in the loss tangent main peak temperature indicated a reduction in the mobility of the long-chain segments containing neutralized acid groups. The stack compaction observed by wide-angle X-ray scattering and transmission electron microscopy in the Cloisite 30B based NCs was attributed to the partial degradation of the surfactant and to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Enhancement of clay dispersion was reported using polyethylene (PE) ionomers ( i.e . ammonium carboxylate polyampholytes prepared from polyethylene (PE)‐graft‐maleic anhydride (PE‐ g ‐MA)) as matrix and using poly(ethylene‐co‐methacrylic acid) ionomer as matrix or as compatibilizer in PE/organomodified clay nanocomposites and in PP/organomodified clay nanocomposites . Similar improvement of clay dispersion in PP/organomodified clay nanocomposites was obtained using, as compatibilizer, PP‐ g ‐MA ionomer neutralized by potassium hydroxide .…”
Section: Introductionmentioning
confidence: 67%
“…Enhancement of clay dispersion was reported using polyethylene (PE) ionomers ( i.e . ammonium carboxylate polyampholytes prepared from polyethylene (PE)‐graft‐maleic anhydride (PE‐ g ‐MA)) as matrix and using poly(ethylene‐co‐methacrylic acid) ionomer as matrix or as compatibilizer in PE/organomodified clay nanocomposites and in PP/organomodified clay nanocomposites . Similar improvement of clay dispersion in PP/organomodified clay nanocomposites was obtained using, as compatibilizer, PP‐ g ‐MA ionomer neutralized by potassium hydroxide .…”
Section: Introductionmentioning
confidence: 67%
“…As was mentioned elsewhere, the good mechanical properties of PP–AII composites can be ascribed not only to the effects of crosslinking, due to the formation of clusters of Zn ionomer, but also to the existence of good compatibility between the PP matrix and filler. Additionally, it is not excluded that the pendant ionic groups in the ionomer might increase the polarity of PP [ 66 , 67 , 89 ], and this plays a key role in improving the interactions with AII. As in the case of other ionomers, Zn ionomer can act as a compatibilizer, allowing a finer filler dispersion and better adhesion between the PP and AII microparticles [ 66 , 67 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…For compatibilization and to obtain enhancements of proprieties, the PP/AII compositions have been modified with selected reactive modifiers, such as PP functionalized/grafted with maleic anhydride (PP-g-MA), and an ionomeric monomeric additive, zinc diacrylate. In fact, fillers such as talc, calcium carbonate, and AII are polar in nature; therefore, for better interfacial adhesion (PP–filler), the modification of PP can be accomplished by attaching polar groups onto the PP backbone, e.g., via the addition of PP-g-MA [ 64 , 65 ], or using metallic ionomers (i.e., zinc diacrylate to lead to Zn ionomer) [ 66 , 67 ], experimental methods often considered in prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum MMT content was low (4.4%), and the phase behavior of the matrix was not reported. In a previous report on the dispersion of OMMT's using a single MMT content,29 pure Pema‐Zn was shown to be more effective than the Pema‐Li in dispersing organoclays. Moreover, it was shown that the Cloisite 20A organoclay was the most adequate organic modification for achieving dispersion when using this ionomer.…”
Section: Introductionmentioning
confidence: 91%